Waterborne diseases that are sensitive to climate variability and climate change - Semenza, Jan C.; Ko, Albert I. (The New England journal of medicine, 2023)
The authors discuss adaptive strategies for reducing the risk of climate-sensitive waterborne diseases, such as climate-proofing water treatment and distribution systems and improving early-warning systems.
Gesehen am 04.11.2024